2016
DOI: 10.1080/21541248.2016.1235386
|View full text |Cite
|
Sign up to set email alerts
|

Nuf and Rip11 requirement for polarity determinant recycling duringDrosophiladevelopment

Abstract: A tight relationship between apico-basal polarity and trafficking is essential for epithelial physiology and tissue homeostasis. Recent studies have described how some Rab GTPases, key components of the intracellular traffic machinery, contribute to the establishment of cell polarity in vertebrates. We have demonstrated a novel connection between cell polarity and trafficking: in Drosophila epithelia, the apical determinant aPKC is recycled via Rab11-Nuf-recycling endosomes to maintain cell polarity. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…7). Rab11 has multiple effectors (Dusty-like protein, Rip11) in addition to NUF (Nagaraj & Adler, 2012;Calero-Cuenca & Sotillos, 2018). These other effectors may be involved in PTTH secretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7). Rab11 has multiple effectors (Dusty-like protein, Rip11) in addition to NUF (Nagaraj & Adler, 2012;Calero-Cuenca & Sotillos, 2018). These other effectors may be involved in PTTH secretion.…”
Section: Discussionmentioning
confidence: 99%
“…NUF is a Rab11 effector protein that is important in controlling the transmission of several intracellular cargos (Riggs et al, 2007;Calero-Cuenca & Sotillos, 2018).…”
Section: Anti-b Mori Nuf Antibodies and Location Of Nuf Immunoreactivitymentioning
confidence: 99%
“…One study demonstrated that a conditional knockout of Rab11fip5 in mice causes the failure of AMPA receptor recycling, resulting in severe long-term neuronal depression ( Bacaj et al, 2015 ). Another study suggested that Rab11fip5 is involved in aPKC recycling to regulate cell polarity in Drosophila ectoderm ( Calero-Cuenca and Sotillos, 2018 ).…”
Section: Discussionmentioning
confidence: 99%